Prospect. 3. - de Gele Zaal, Gent (Gent : Noordstarfonds vzw, 1986)
Beyls, Peter ; Engeln, Franklin ; Engels, Trudo ; Vanpevenaege, Yves ; Vuylsteke, Jaak
Prospect. 3, De Gele Zaal, Gent, 27.10 - 2.11.1986
boek